Mental Burden on Students During Online Lectures - Tambun, Madschen SMOSS; Patrisia, Yolanda (Journal of Humanities and Social Sciences (JHASS), 2022)
Pandemi COVID-19 telah menjadi perhatian di seluruh dunia. Kebijakan dalam rangka pencegahan penyebaran virus seperti pembelajaran online juga diberlakukan pada mahasiswa. Mahasiswa yang mengikuti pembelajaran online mayoritas mengalami keluhan beban kerja mental. Metode penelitian ini adalah literatur review dengan menghasilkan 11 artikel penelitian. Pada umumnya untuk meneliti beban kerja mental pada mahasiswa, menggunakan metode NASA-TLX dimana tingkat validitas dan reliabilitas lebih tinggi dan sudah teruji pada banyak penelitian. Dari 11 jurnal, responden (mahasiswa) mengalami beban mental selama pembelajaran daring. Kategori beban mental berada pada tingkat tinggi dan sedang. Mental Burden on Students During Online Lectures Abstract: COVID-19 pandemic has become an international concern. Policies to prevent the spread of disease, such as learning from home, are applied to university students. Students who follow online learning the majority experience mental workload complaints. This research method is a review literature by producing 11 research articles. In general, to research the mental workload in students, using the NASA-TLX method where the level of validity and reliability is higher and has been tested in many studies. Of the 11 journals, respondents (students) experienced mental burdens during online learning. The mental load category is at high and moderate levels. Keywords: COVID-19, Mental Burden, Online Lectures, Students.